Intrathecal magnetic drug targeting for localized delivery of therapeutics in the CNS. (April 2017) - Venugopal, Indu; Habib, Nazia; Linninger, Andreas
Aim: The challenge in treating neurological diseases is not lack of drug potency, but ineffective targeting techniques. We propose a technique called intrathecal magnetic drug targeting (IT-MDT), in which intrathecally injected magnetic nanoparticles (MNPs) are targeted to specific sites using external magnets.Materials & methods: MRI and histology confirmed localization of MNPs via IT-MDT at target sites along the spine of Sprague–Dawley rats.Results : MRI results confirmed greater MNP localization when the duration of magnet application was extended. Histological analysis quantified MNP tissue uptake and provided insight into their route of transport into deeper tissue regions.Conclusion: IT-MDT has potential for future use in neurological disease treatments. It can produce localized therapeutic effect, with decreased systemic toxicity.